[PP.36.05] EXPRESSION AND CHANGE IN MIRS 145, 221 AND 222 EXPRESSION IN HYPERTENSIVE SUBJECTS TREATED WITH ENALAPRIL, LOSARTAN OR OLMESARTAN. (September 2016) - Aragona, C.O.; Mandraffino, G.; Cairo, V.; Mamone, F.; Quartuccio, S.; D'Ascola, A.; Scuruchi, M.; Gullo, A.L.o; Saitta, A.; Imbalzano, E.
Abstract : Objective: To evaluate whether the anti-hypertensive drugs enalapril, losartan or olmesartan may have effects on monocyte expression of different microRNAs (miRs 145, 221 and 222) involved in vasculature homeostasis and damage, in essential hypertensives. Design and method: Sixty-four essential hypertensives without organ damage nor additional risk factor for CVD and 42 controls were included; we evaluated blood pressure (SBP/DBP), lipid profile, fasting glucose, C-reactive protein (CRP), fibrinogen, arterial stiffness (AS) indices (pulse way velocity: PWV; augmentation index: AIx) and carotid intima-media thickness (cIMT) at baseline (T0) and after 24-weeks treatment (T1). Subjects with plasma levels of low-density lipoprotein cholesterol (LDL-C) >160 mg/dl, triglycerides (TG) >200 mg/dl, body mass index (BMI) >30, alcohol consumption, a personal or familial history of CVD, diabetes mellitus, or thyroid, liver or kidney diseases were excluded. Patients were randomly assigned to receive once a day enalapril 20 mg, losartan 100 mg or olmesartan 20 mg. Comparisons were carried out by Wilcoxon test (T1 vs T0), Kruskall-Wallis (multiple comparisons), and Mann-Whitney (comparisons between paired treatment arms). A two tailed p of 0.05 was considered for significance. Results: T1: we found a significant improvement of both SBP/DBP (SBP: −19.03%, p < 0.001; DBP: −14.41%, p < 0.001), lipid profile (HDL-C: +4.4%, and LDL-C: −6.4%; both p < 0.001), glucose (−2.5%, p < 0.001), BMI (−3.1%, p < 0.001), fibrinogen (−6.2%, p < 0.001), CRP (−9.2%, p < 0.005), AIx (−19.1%, p < 0.001); PWV (−14.4%, p < 0.001), and miR expression (miR221: −29.8%, miR222: −39.7%, miR145: +41.1%; all p < 0.001). We compared the effects on different variables by analyzing separately each arm of treatment: olmesartan appeared the most effective in reducing CRP (−9.48%), and miRs221/222 (−32.9% and −42.4%, respectively); losartan reduced PWV (−37.6%) and improved HDL-C (+7.9%) and miR145 (+51.5%) more than olmesartan and enalapril; enalapril appeared more effective on fibrinogen reduction (−9%); no differences were found as regards BMI, glucose, LDL-C, SBP, DBP, AIx, and cIMT. Conclusions: Enalapril, losartan and olmesartan are effective in improving mechanical and humoral factors associated to AS and atherogenesis; these drugs restored in untreated hypertensives the deregulated connection between miRs221/222 and miR145, thus contributing to slow the progression of vascular damage already shown in the clinical studies.